Mother tongue phonological interference in english language speech. - Jami Jami, Juan Carlos (2016)
The main aim of this qualitative research was to analyze the mother tongue phonological interference in English language speech in an elementary level. In a first stage, the literature review permitted to approach the main topics for understanding if the mother tongue phonological interference could be considered a problem in the second language learners’ pronunciation. To do that, the researchers found the most difficult sounds in which learners always present problems affecting their pronunciation. In a second stage, the observation to students of the level A2 of the Language Cultural Center at Technical University of Cotopaxi was applied to identify if they presented the mother tongue phonological interference at the moment of articulating English sounds. Field notes sheets were used to obtained some word sounds’ difficult to articulate by students in which they presented mother tongue phonological interference. Those sounds were adapted to elaborate the checklist in order to evaluate the mother tongue phonological interference. Thus, data from the instrument showed that the majority of participants present the mother tongue phonological interference because they used Spanish sounds during the pronunciation of certain sounds in English. Based on the literature review, the researchers present L1 and L2 equivalence of sounds between Spanish and English as a teaching strategy to reduce the phonological interference. This qualitative research denotes a relevant importance because it allows reflecting on a key point that had been forgotten but it is necessary for improving the English pronunciation. Overall, the mother tongue phonological interference must be taken in account by teachers during the class to help students to overcome these learning problems.